Popper’s Negative Utilitarianism and the Ethics of African Humanism - Ifeanyichukwu Ogbodo, Ignatius; Anichebe, Obiora; Ohabuenyi Abah, George (International Journal of Psychosocial Rehabilitation, 2024)
This paper deals on Karl Popper’s Negative Utilitarianism and the Ethics of African Humanism. It examines Popper’s concept of Negative Utilitarianism with a view to using Popper’s Negative Utilitarianism as a tool for the analysis of an Ethics of African Humanism. Popper’s Negative Utilitarianism asserts that the principal business of politics is to reduce suffering rather than to increase happiness. The function of ethics African humanism, in this regard, is to drive social and political reform that should work for the elimination of concrete evils. The objective is to elucidate Popper’s negative utilitarian with a view to directing Ethics of African Humanism to proffer values proper to Africa, which can drive governance to focus not on establishing happiness through massive utopian planning, rather to aim at the elimination of immediate concrete miseries of the African people by means of piecemeal tinkering. This paper adopts hermeneutical, expository and textual analysis methods. This paper shows that adopting the method of elimination of false theories will help ethics of African Humanism to cast light on governance to concentrate on gradual elimination of social situation that increase suffering of the greatest number, rather than concentrate on Policies that increase the happiness or serve the interest of only a section of a nation.